2014
DOI: 10.1097/hjh.0000000000000122
|View full text |Cite
|
Sign up to set email alerts
|

Validation and comparison of three formulae to estimate sodium and potassium excretion from a single morning fasting urine compared to 24-h measures in 11 countries

Abstract: In a diverse population, the Kawasaki formula is the most valid and least biased method of estimating 24-h sodium excretion from a single MFU and is suitable for population studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
138
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(151 citation statements)
references
References 24 publications
8
138
1
4
Order By: Relevance
“…417 In the Prospective Urban Rural Epidemiology (PURE) study, which used samples from 11 countries, including many Asians, the Kawasaki equation instead was the best fit. 418 Most investigators [418][419][420] found that although corrected spot urines may be sufficient to estimate mean population sodium excretion levels, there was substantial disagreement between the measures for individuals. Hence, spot urines, which exhibit increased variability compared with actual 24-hour measurements, should be considered inadequate for the assessment of sodium excretion in research studies dealing with SSBP.…”
Section: Measurement Of Sodium Intake/excretion and Assessment Of Ssbpmentioning
confidence: 99%
“…417 In the Prospective Urban Rural Epidemiology (PURE) study, which used samples from 11 countries, including many Asians, the Kawasaki equation instead was the best fit. 418 Most investigators [418][419][420] found that although corrected spot urines may be sufficient to estimate mean population sodium excretion levels, there was substantial disagreement between the measures for individuals. Hence, spot urines, which exhibit increased variability compared with actual 24-hour measurements, should be considered inadequate for the assessment of sodium excretion in research studies dealing with SSBP.…”
Section: Measurement Of Sodium Intake/excretion and Assessment Of Ssbpmentioning
confidence: 99%
“…24 When using a fasting urine sample, the Kawasaki formula-derived estimates produce the least biased estimates of sodium intake (intraclass correlation of 0.71 for Kawasaki formula estimated 24-hour sodium excretion compared with actual 24-hour urinary collections), based on an international validation study in 11 countries. 25 In other settings, for example, when using a nonfasting sample, that Kawasaki formula is associated with more biased estimates than other formula which were developed for use of spot random samples. 24 Therefore, the type of sample collected (time and fasting status), population included, and formula used are important considerations.…”
Section: Methods Of Measuring Sodium Intakementioning
confidence: 99%
“…3 The PURE study did attempt to validate spot urine sodium to 24-hour urine sodium and found a moderate association; however, that validation study also had concerning methodological and quality control issues. 4,5 The study included 24-hour urine samples within 25% of predicted 24-hour excretion of creatinine as being complete even though the original method called for excluding urine that exceeded 15% of predicted creatinine excretion. 6 There was no rationale provided for revising the criteria for assessing complete urine collection but, even with the revised criteria, only 50% of 24-hour urine samples were "complete."…”
mentioning
confidence: 99%